Burning mouth syndrome caused by xerostomia secondary to amlodipine - Tengku Natasha Eleena binti Tengku Ahmad Noor (Dental Journal (Majalah Kedokteran Gigi), 2020)
Background: Xerostomia, generally referred to as dry mouth, has been identified as a side effect of more than 1,800 drugs from more than 80 groups. This condition is frequently unrecognised and untreated but may affect patients’ quality of life and cause problems with oral and medical health, including burning mouth syndrome (BMS). Purpose: The purpose of this case is to discuss how to manage a patient with BMS caused by xerostomia secondary to medication that has been taken by the patient. Case: We reported that a 45-year-old male military officer from the Royal Malaysian Air Force came to Kuching Armed Forces Dental Clinic with dry mouth and a burning sensation since he started taking 10 mg of amlodipine due to his hypertension. After a thorough physical and history examination, we made a diagnosis of burning mouth syndrome (BMS) caused by xerostomia secondary to amlodipine. Case Management: Oral hygiene instructions, diet advice and prescription of Oral7 mouthwash has been given to reduce the symptoms of BMS. The patient has been referred to the general practitioner to reduce his amlodipine dosage from 10 mg to 5 mg (OD) in order to prevent xerostomia, and oral hygiene instructions have been given. A review after two weeks showed significant changes in the oral cavity, and the patient was satisfied as he is no longer feeling the burning sensation and can enjoy his food without feeling difficulty in chewing and swallowing. Conclusion: Adverse drug events are normal in the oral cavity and may have a number of clinical presentations such as xerostomia. Xerostomia can cause many implications as saliva helps in maintaining oral mucosa and has a protective function. The signs of adverse drug incidents in the oral cavity should be identified to oral health care professionals.